A Hybrid Collision Resolution Protocol for Passive RFID Tag Identification. (2009) - Xin-qing Xin-qing, Yan Yan; Zhou-ping Zhou-ping, Yin Yin; You-lun You-lun, Xiong Xiong
Abstract : Wireless communication channel collision of RFID system is a key issue that affects the pervasive application of the system, especially for passive RFID system due to the constrained communication ability and energy supply of tags. The collision resolution protocols suggested can be categorized into deterministic tree based protocols and probabilistic frame slot ALOHA based protocols. A hybrid protocol, which combines the query tree protocol and dynamic framed slotted ALOHA protocol, is presented here. In this protocol, at the beginning of each identification frame, the reader broadcasts a query command message which contains a suffix string and integer to indicate a frame size used in this frame to all tags in its vicinity, and every tag whose data match the specified suffix string randomly selects a slot in the frame to transmit its data to the reader. After each round, based on the different occupying situation of slots, the reader re-estimates the number of tags in its range, and according to the identification accuracy required, decides whether to split the group of tags to be identified into sub-groups or not, and adjust the suffix string and select a suitable frame size for the command messages of the following frames. Through this repeated identification and division process, the RFID tags can be identified within a number of frames. Some key factors that influence the efficiency of the identification are also discussed based on binomial distribution model. Three methods for the tag population estimation are examined and their accuracies are compared, and the optimum frame size for the identification of different number of tags is given in consideration of the throughput and efficiency. To verify the performance of the hybrid protocol, a numeric simulation is performed, in which 100 groups of SGTIN-96 encoded tags are generated randomly. Simulation shows that this hybrid protocol outperforms other frame slot ALOHA based collision resolution protocols, especially when there are a large number of RFID tags to be identified. The overall throughput of the hybrid protocol is kept around 34.8% when there are more than 40 tags, near the theoretical maximum value 36.8%. A linear relationship between the number of tags and the total frames and slots required is also observed in the numeric simulation.